Effect of chemical admixtures on the properties of grouting materials with high-volume mineral materials. (11th December 2019) - Li, Xianjun
Based on the preparation of grouting materials with high-volume mineral admixtures, the effects of chemical admixtures including early-strength components and retarding components on the grouts with volume mineral admixtures were investigated. The results show that early-strength components have little effect on the grouts with high-volume mineral admixtures. Retarding component sodium gluconate does not play a great role for the grouts with high-volume mineral admixtures. However, the incorporation of borax and sodium tripolyphosphate can greatly improve the properties of the grouts, mainly due to their composite effect. The appropriate compound content is 0.4 wt% borax and 0–0.2 wt% sodium tripolyphosphate of cementitious materials. When 0.4 wt% borax and 0.2 wt% sodium tripolyphosphate were added to the grouts with volume mineral admixtures, initial fluidity and 30-min fluidity are 340 mm, and 1-, 3-, and 28-day compressive strength are, respectively, 41.6, 57.1, and 81.5 MPa. These values far exceed the standard requirements. It also shows that early-strength components and sodium gluconate can be neglected when high-volume mineral admixtures are added to the grouts.